Svensk tjänstehundsavel : en återblick och nutidsbeskrivning samt förslag inför framtiden - Lorentzon, Patrik (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2008)
In 1936 a governmental breeding project was started with aim on military use. The police later came to use dogs from this project as well. In order to utilize dogs that could fit for other purposes training and education of dogs for search of different substances and of guide dogs for blind persons was performed. A political decision to privatize the whole dog programme was taken in 1992.